PDGFR Inhibition Results in Pericyte Depletion and Hemorrhage into the Corpus Luteum of the Rat Ovary. (January 2016) - Hall, Anthony P.; Ashton, Susan; Horner, Judith; Wilson, Zena; Reens, Jaimini; Richmond, Graham H. P.; Barry, Simon T.; Wedge, Steve R.
The growth plate, ovary, adrenal gland, and rodent incisor tooth are sentinel organs for antiangiogenic effects since they respond reliably, quantitatively, and sensitively to inhibition of the vascular endothelial growth factor receptor (VEGFR). Here we report that treatment of rats with platelet-derived growth factor receptor beta (PDGFRβ) inhibitors that target pericytes results in severe ovarian hemorrhage with degeneration and eventual rupture of the corpus luteum. Evaluation of the growth plate, adrenal gland, and incisor tooth that are typical target organs for antiangiogenic treatment in the rodent revealed no abnormalities. Histologically, the changes in the ovary were characterized by sinusoidal dilatation, increased vessel fragility, and hemorrhage into the corpus luteum. Immunocytochemical staining of vessels with alpha smooth muscle actin and CD31 that recognize pericytes and vascular endothelium, respectively, demonstrated that this effect was due to selective pericyte deficiency within corpora lutea. Further experiments in which rats were treated concurrently with both PDGFRβ and VEGFR inhibitors ablated the hemorrhagic response, resulting instead in corpus luteum necrosis. These changes are consistent with the notion that selective pericyte loss in the primitive capillary network resulted in increased vessel fragility and hemorrhage, whereas concomitant VEGFR inhibition resulted in vessel regression and reduced vascular perfusion that restricted development of the hemorrhagic vessels. These results also highlight the utility of the rodent ovary to respond differentially to VEGFR and PDGFR inhibitors, which may provide useful information during routine safety assessment for determining target organ toxicity.